Misunderstandings in ART Triadic Interactions: A Qualitative Comparison of First and Follow-Up Visits - Rossi, Maria Grazia; Vegni, Elena; Menichetti, Julia (Frontiers in Psychology, 2021)
Background: Misunderstandings in medical interactions can compromise the quality of communication and affect self-management, especially in complex interactions like those in the Assisted Reproductive Technology (ART) field. This study aimed to detect and describe misunderstandings in ART triadic visits. We compared first and follow-up visits for frequency, type, speakers, and topics leading to misunderstandings. Methods: We purposively sampled 20 triadic interactions from a corpus of 85 visits. We used a previously developed coding scheme to detect different types of misunderstandings (i.e., with strong, acceptable, and weak evidence). We analyzed also the different topics leading to strong misunderstandings (direct expressions of lack of understanding, pragmatic alternative understandings, semantic alternative understandings) to provide insights about the contents of the consultation that may need particular attention and care. Findings: We detected an overall number of 1078 misunderstandings in the 20 selected visits. First visits contained almost two-third of the misunderstandings (n = 680, 63%). First visits were particularly rich in misunderstandings with acceptable evidence (e.g. clarifications and checks for understanding), compared to follow-up visits. In first visits, doctors’ turns more frequently than couples’ turns contained misunderstandings, while in follow-up visits it was the other way around. Looking at the couple, the majority of the misunderstandings were expressed by the woman (n = 241, 22%) rather than by the man (n = 194, 18%). However, when weighting for their number of turns, 9% of the men’s turns included an expression of misunderstanding, compared to the 7% of the women’s turns. Finally, more than half of the misunderstandings with strong evidence were about history-taking and treatment-related topics, and while the history-taking ones were particularly frequent in first visits the treatment-related ones were more present in follow-up visits. Discussion: Findings indicate that first visits may deserve particular attention to avoid misunderstandings, as they are the moment where a shared understanding can be harder to reach. In particular, misunderstandings happening in first visits seem mostly related to physicians having to reconstruct the clinical history of patients, whilst those in the follow-up visits seem to reflect residual and unsolved doubts from the couple, especially concerning treatments.